PERANCANGAN PERAWATAN DAN PENJADWALAN PREVENTIVE MAINTENANCE MESIN STITCHING BERBASIS METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI CV MADYOTOMO: PERANCANGAN PERAWATAN DAN PENJADWALAN PREVENTIVE MAINTENANCE MESIN STITCHING BERBASIS METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI CV MADYOTOMO - Costa, Lourdes Alice Soares; Agusti, Febrina; Utami, Indah Wahyu (Universitas Duta Bangsa Surakarta, 2025)
This study intends to create a system for maintenance and a schedule for preventive maintenance for the sewing machine at CV Madyotomo by utilizing the Reliability Centered Maintenance (RCM) approach. The main problem is the high downtime of the Müller Martini 321 stitching machine, which reached 20,114 minutes during January–June 2025, resulting in a production capacity loss of 1,005,711 books and an estimated financial loss of around Rp50,285,550. The research method involved identifying critical components through observation, interviews, and Failure Mode and Effect Analysis (FMEA), followed by the calculation of Mean Time To Failure (MTTF), Mean Time To Repair (MTTR), and failure distribution using Minitab 19 software. The results indicate four critical components with the highest Risk Priority Number (RPN), namely bearing (240), v-belt (189), shaft gear (175), and support gear (160). Based on the analysis, the optimal preventive maintenance intervals are bearing every 18 days, v-belt every 21 days, shaft gear every 21 days, and support gear every 28 days, with MTTF values ranging from 693 to 1,174 hours and MTTR averaging 4–6 hours. The implementation of an RCM-based preventive maintenance strategy is proven to reduce downtime, improve machine reliability, and ensure production efficiency, thus providing a guideline for printing companies in formulating measurable, effective, and efficient maintenance policies.